Staging Anti-Inflammatory Therapy in Alzheimer's Disease - Galea, Elena (Frontiers in Aging Neuroscience, 2010)
The use of non-steroidal anti-inflammatory drugs (NSAIDs) in Alzheimer's disease (AD) is controversial because conclusions from numerous epidemiological studies reporting delayed onset of AD in NSAID users have not been corroborated in clinical trials. The purpose of this personal view is to revise the case for NSAIDs in AD therapeutics in light of: (i) the last report from the only primary prevention trial in AD, ADAPT, which, although incomplete, points to significant protection in long-term naproxen users, and (ii) the recently proposed dynamic model of AD evolution. The model contends that there is a clinical silent phase in AD that can last up to 20 years, the duration depending on life style habits, genetic factors, or cognitive reserve. The failure of many purported disease-modifying drugs in AD clinical trials is forcing the view that treatments will only be efficacious if administered pre-clinically. Here we will argue that NSAIDs failed in clinical trials because they are disease-modifying drugs, and they should be administered in early stages of the disease. A complete prevention trial in cognitively normal individuals is thus called for. Further, the shift of anti-inflammatory treatment to early stages uncovers a knowledge void about the targets of NSAIDs in asymptomatic individuals. AD researchers have mostly relied on post-mortem analysis of Aβ plaque-laden brains from demented patients or animal models, thus drawing conclusions about AD pathogenesis based on late symptoms. We will discuss evidence in support that defective, not excessive, inflammation underlies AD pathogenesis, that NSAIDs are multifunctional drugs acting on inflammatory and non-inflammatory targets, and that astrocytes and microglia may play differing roles in disease progression, with an emphasis of ApoEε4 as a key, undervalued target of NSAIDs. According to a meta-analysis of epidemiological data, NSAIDs afford an average protection of 58%. If this figure is true, and translated into patient numbers, NSAID treatment may revive as a worth pursuing strategy to significantly reduce the socio-economical burden imposed by AD.